2022
DOI: 10.1098/rspb.2021.2538
|View full text |Cite
|
Sign up to set email alerts
|

Fungal ectoparasites increase winter mortality of ladybird hosts despite limited effects on their immune system

Abstract: Winter represents a challenging period for insects inhabiting temperate regions. A plethora of studies have investigated how environmental conditions such as temperature affect insect overwintering success. However, only a few studies have focused on biotic factors and the mechanisms affecting the overwintering performance of insects. Here, we investigated the effects of the parasitic fungus Hesperomyces virescens on the overwintering performance and immune system functioning of the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Our overwintering studies demonstrated that more H. halys that died while overwintering contained spores of N. maddoxi and/or C. fioriniae than H. halys surviving overwintering, strongly suggesting that adults infected with these fungal pathogens had a greater chance of mortality during overwintering. Among individuals of the coccinellid Harmonia axyridis (Pallas) infected with the ectoparasitic fungus, Hesperomyces virescens Thaxter, higher mortality in infected versus healthy insects occurred while overwintering ( Knapp et al 2022 ). These experimental studies with ladybeetles suggested that a mix of energy exhaustion and decreased immune response were responsible for the increased mortality of infected H. axyridis while overwintering.…”
Section: Discussionmentioning
confidence: 99%
“…Our overwintering studies demonstrated that more H. halys that died while overwintering contained spores of N. maddoxi and/or C. fioriniae than H. halys surviving overwintering, strongly suggesting that adults infected with these fungal pathogens had a greater chance of mortality during overwintering. Among individuals of the coccinellid Harmonia axyridis (Pallas) infected with the ectoparasitic fungus, Hesperomyces virescens Thaxter, higher mortality in infected versus healthy insects occurred while overwintering ( Knapp et al 2022 ). These experimental studies with ladybeetles suggested that a mix of energy exhaustion and decreased immune response were responsible for the increased mortality of infected H. axyridis while overwintering.…”
Section: Discussionmentioning
confidence: 99%
“…The ladybird Harmonia axyridis serves as a popular model species because of its invasive success worldwide (Brown et al, 1997;Roy et al, 2016) and because a significant amount of knowledge on its biology and behaviour has been accumulated through extensive studies (Hodek et al, 2012;Awad et al, 2015a;Awad et al, 2017;R ̌erǐcha et al, 2021). During our own laboratory and field investigations focused on various aspects of ladybird biology (e.g., Knapp et al, 2019;Knapp et al, 2022), we repeatedly observed attempts to mate with dead conspecifics in Harmonia axyridis during the growing season and post-overwintering period.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the observations presented here and their potential significance (conserving native species biodiversity and reducing disease transmission), it would be worthy to consider examining reproductive interference in closely related taxa (perhaps to tribe, as seen here) when considering biocontrol plans involving lady beetles. Also, as reproductive interference can also result in indirect effects such as the transmission of diseases and parasites (Hurst et al 1995;Knapp et al 2022;Nalepa and Weir 2007;Webberley et al 2006), these should also be considered. The apparent increase in the dissemination of Hesperomyces spp.…”
mentioning
confidence: 99%
“…by H. axyridis is facilitated by their winter aggregation behavior, but it is also considered a sexually-transmitted “disease” (Nalepa et al 2007). Although behavioral changes in hosts are not known to be caused by Hesperomyces spp., they can impair their fitness (Knapp et al 2022) and increase their susceptibility to infection by entomopathogens (Haelewaters et al 2020). Moreover, other fungi in the order Laboulbeniales have been found to cause behavioral changes in ants (Báthori et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation